Novel metabolomic profile of subjects with non-classic apparent mineralocorticoid excess - Alejandra Tapia-Castillo (Nature Portfolio, 2021)
Abstract Nonclassic apparent mineralocorticoid excess (NC-AME) is proposed as a novel clinical condition with a mild phenotypic spectrum that ranges from normotension to severe hypertension. This condition is mainly characterized by a high serum cortisol to cortisone ratio (F/E) and concomitant low cortisone (E), however further metabolic changes in NC-AME have not been studied. A cross-sectional study was performed in a primary-care cohort of 396 Chilean subjects, which were classified in two groups: NC-AME (n = 28) and healthy controls (n = 27). A discovery study based in untargeted metabolomics assay in serum samples from both groups was performed by UPLC-Q-TOF/MS. Global metabolomic variations were assayed by principal component analysis and further compared by orthogonal partial least-squares discriminant analysis (OPLS-DA). NC-AME subjects exhibited higher values of blood pressure, fractional excretion of potassium, and lower plasma renin activity and urinary sodium to potassium ratio. Metabolomic analyses showed 36 differentially regulated metabolites between NC-AME and control subjects. A ROC curve analyses identified eight metabolites with high discriminatory capacity between NC-AME and control subjects. Moreover, gamma-l-glutamyl-l-methionine sulfoxide and 5-sulfoxymethylfurfural, exhibited significant association with cortisone, which are potential biomarkers of NC-AME, however further assays should elucidate its biological role in setup and progression of this phenotype.